P38 MAPK pathway is essential for self‐renewal of mouse male germline stem cells (mGSCs). (21st November 2016) - Niu, Zhiwei; Mu, Hailong; Zhu, Haijing; Wu, Jiang; Hua, Jinlian
Abstract: Objectives: Male germline stem cells (mGSCs), also called spermatogonial stem cells (SSCs), constantly generate spermatozoa in male animals. A number of preliminary studies on mechanisms of mGSC self‐renewal have previously been conducted, revealing that several factors are involved in this regulated process. The p38 MAPK pathway is widely conserved in multiple cell types in vivo, and plays an important role in cell proliferation, differentiation, inflammation and apoptosis. However, its role in self‐renewal of mGSCs has not hitherto been determined. Materials and methods: Here, the mouse mGSCs were cultured and their identity was verified by semi‐RT‐PCR, alkaline phosphatase (AP) staining and immunofluorescence staining. Then, the p38 MAPK pathway was blocked by p38 MAPK‐specific inhibitor SB202190. mGSC self‐renewal ability was then analysed by observation of morphology, cell number, cell growth analysis, TUNEL incorporation assay and cell cycle analysis. Results: Results showed that mouse mGSC self‐renewal ability was significantly inhibited by SB202190. Conclusions: This study showed for the first time that the p38 MAPK pathway plays a key role in maintaining self‐renewal capacity of mouse mGSCs, which offers a new self‐renewal pathway for these cells and contributes to overall knowledge of the mechanisms of mGSC self‐renewal.